Administrative Acts Completely Removed from the Control of the Legality of the Administrative Contentious Courts - Ieremie, Maria-Cristiana (Journal of Danubian Studies and Research, 2023)
With the appearance and establishment of the administrative contentious, the issue of the existence of an absolute right of control of the courts over administrative acts arose. This presumption gained momentum when these new norms materialized, but the legislator, through the numerous normative acts, completely dismantled this attempt. In this article we will analyze which are in fact, the administrative acts that are completely removed from the legality control of the administrative contentious courts.